Erosive pustular dermatosis of the scalp successfully treated with oral prednisone and topical tacrolimus - Mariana Ribas Zahdi; Gabriela Bestani Seidel; Vanessa Cristina Soares; Camila Fernanda Novak Pinheiro de Freitas; Fabiane Andrade Mulinari-Brenner (Sociedade Brasileira de Dermatologia, 2013)
Erosive pustular dermatosis of the scalp is a rare inflammatory disorder of the scalp, affecting elderly patients after local trauma and leading to scarring or cicatricial alopecia. Case Report: An elderly female patient complained of painful pustules on the parietal region bilaterally with progressive enlargement and ulceration. A biopsy suggested erosive pustular dermatosis of the scalp and the patient was treated with prednisone 40 mg/day and 0.1% topical tacrolimus. After 10 weeks complete closure of the eroded areas was observed and a stable scarring alopecia developed.